Marketing mix factors affecting consumers’ decision on the choice of food delivery application services - Kongchan, Ananchai; Praphanphoj, Veerachai (KASEM BUNDIT JOURNAL, 2025)
PURPOSES: To study the influence of marketing mix factors on the choice of food delivery application service of consumers in Bangkok Metropolitan Region, and compare the use of the services of consumers in Bangkok Metropolitan Region by demographics factors. METHODS: Sample survey research of 400 samples by means of accidental sampling and questionnaire as a tool for data collection. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, one-way variance analysis and multiple regression analysis. RESULTS: Food delivery applications were very important in consumers’ decision on purchase of delivery food. The marketing mix of price, channel, people, and physical composition positively and significantly effected the choice of a food delivery application and could predict the decision behavior by 74.20%. Moreover, demographic factors i.e. sex, age, occupation, education, and income also affected the decision in choosing food application services. THEORETICAL/ POLICY IMPLICATIONS: Entrepreneurs could develop food delivery applications and apply appropriate marketing strategies to adjust their pricing, channel, personnel, and physical composition to attract consumers’ decision on purchase of delivery food. Marketers should communicate directly to their target consumers based on their individual characteristics to optimize their reach to them.